1999
DOI: 10.1016/s0741-5214(99)70036-4
|View full text |Cite
|
Sign up to set email alerts
|

Results of elective abdominal aortic aneurysm repair in the 1990s: A population-based analysis of 2335 cases

Abstract: Elective AAA repair is a safe procedure in contemporary practice in Maryland. Operative risk is increased among the elderly and when operations are performed by surgeons with very low volumes or in low-volume hospitals. Hospital lengths of stay were shorter and charges were lower when elective AAA repair was performed by surgeons with higher volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
151
4
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(176 citation statements)
references
References 39 publications
12
151
4
9
Order By: Relevance
“…Although age has been considered a minor clinical predictor by the ACC/AHA classification 28 , in our study it correlated in a statistically significant way with early morbidity and mortality, in accordance with other studies 12,[30][31][32] .…”
Section: Discussionsupporting
confidence: 92%
“…Although age has been considered a minor clinical predictor by the ACC/AHA classification 28 , in our study it correlated in a statistically significant way with early morbidity and mortality, in accordance with other studies 12,[30][31][32] .…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown that, in the past two decades, the hospital and surgeon volume are closely associated with better surgical outcome with lower postoperative complications or mortalities, such as paediatric cardiac surgery, 4 repair of abdominal aortic aneurysm, 5 coronary artery bypass graft surgery, 6 ventriculo-peritoneal shunt procedures, 7 total hip replacement surgery, 8 and colon cancer surgery. 9 However, only few studies reported the relationship between provider volume and the incidence of postoperative endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…La mortalidad asociada a la cirugía por AAA ha disminuido drásticamente en las últimas décadas por el progreso continuo en el diagnóstico, manejo de las patologías asociadas, técnica operatoria y anestesia [3][4][5][6] . Sin embargo, la mortalidad persiste elevada en grupos específicos, particularmente en los pacientes de mayor edad [3][4][5][6][7][8][9][10] El tipo de reconstrucción y procedimientos asociados se exponen en la Tabla 2. La mortalidad global de la serie (operaciones electivas y urgentes) fue 15% (12 pacientes).…”
Section: Resultsunclassified
“…La edad es considerada habitualmente un factor de riesgo importante en todas las experiencias comunicadas, por lo que hay quienes estiman que la cirugía estaría contraindicada en octogenarios. Sin embargo, hay suficiente evidencia de que la morbimortalidad depende en parte de factores predecibles, modificables o controlables [3][4][5][6]8 . Los resultados mostrados en la presente serie son comparables con los publicados en series similares, y están dentro de los estándares internacionales para la cirugía del AAA en poblaciones no seleccionadas 7,9,10 .…”
Section: Discussionunclassified